Assessing transfusion need in patients with type A aortic dissection with multiplate aggregometry. - Biniam Melese Bekele; Sascha Ott; Benjamin O'Brien; Matteo Montagner; Volkmar Falk; Stephan Kurz (PLoS ONE)
Background Acute type A aortic dissection (ATAAD) represents a life-threatening surgical emergency. Use of antiplatelet drugs and platelet dysfunction exacerbate the already high rates of postoperative morbidity and mortality. The objective of this study was to determine the relationship between preoperative platelet function evaluated through Multiplate® aggregometry and transfusion requirement. Methods This observational retrospective study included 180 patients who underwent emergency surgical repair of ATAAD over a two-year period (2019-2021). Platelet function was evaluated preoperatively using Multiplate® analyzer with three activators: adenosine diphosphate (ADP test), arachidonic acid (ASPI test) and thrombin receptor-activating peptide-6 (TRAP test). Primary outcome was the number of blood products transfused. In addition, the need for surgical re-exploration, length of hospital stay and 30-day mortality were compared. Results Abnormal aggregation responses were observed in 89 (49.2%) patients using ASPI test, in 47 (26%) patients using ADP test, and in 113 (63.5%) patients using the TRAP test. Thirty-six (20%) patients exhibited an abnormal response to all three tests. Preoperative use of aspirin was documented in 35 (19.3%) patients, while clopidogrel use was documented in 7 (3.9%) patients. Patients with anormal ADP responses required more intraoperative red cell concentrates (3.4 ± 3.9 versus 2.1 ± 3.2, p = 0.039), intraoperative platelet concentrates (4.2 ± 2.9 versus 3.1 ± 2.4, p = 0.015) and total platelet concentrates (8.1 ± 7.8 versus 6.2 ± 8.1, p = 0.008). There were no significant differences in the need for surgical re-exploration, the total length of hospital stay, or 30-day mortality. Conclusions Multiplate® aggregometry can be a useful tool for evaluating platelet dysfunction and assessing transfusion need in ATAAD patients, thereby aiding in the optimization of treatment strategies.